EEG emotion recognition system - Ma, Li Ya; Quek, Chai; Teo, Kaixiang; Abdul Rahman, Abdul Wahab; Abut, Huseyin (Springer US, 2009)
This chapter proposes an emotion recognition system based on time domain analysis of the bio-signals for emotion features extraction. Three different types of emotions (happy, relax and sad) are classified and results are compared using five different algorithms based on RVM, MLP, DT, SVM and Bayesian techniques. Experimental results show the potential of using the time domain analysis for real-time application.